In vitro and in vivo activities of imipenem combined with BLI-489 against class D β-lactamase-producing Acinetobacter baumannii. (14th October 2020) - Wang, Yung-Chih; Huang, Shu-Wei; Chiang, Ming-Hsien; Lee, I-Ming; Kuo, Shu-Chen; Yang, Ya-Sung; Chiu, Chun-Hsiang; Su, Ying-Shih; Chen, Te-Li; Wang, Fu-Der; Lee, Yi-Tzu
Abstract: Background: According to our preliminary study, BLI-489 has the potential to inhibit the hydrolysing activity of OXA-51-like β-lactamase produced by carbapenem-resistant Acinetobacter baumannii (CRAb). Objectives: In the present study, the in vitro and in vivo activities of imipenem combined with BLI-489 against CRAb producing carbapenem-hydrolysing class D β-lactamases (CHDLs), namely OXA-23, OXA-24, OXA-51 and OXA-58, were determined. Methods: A chequerboard analysis of imipenem and BLI-489 was performed using 57 and 7 clinical CRAb isolates producing different CHDLs and MBLs, respectively. Four representative strains harbouring different CHDL genes were subjected to a time–kill assay to evaluate the synergistic effects. An in silico docking analysis was conducted to simulate the interactions between BLI-489 and the different families of CHDLs. The in vivo activities of this combination were assessed using a Caenorhabditis elegans survival assay and a mouse pneumonia model. Results: Chequerboard analysis showed that imipenem and BLI-489 had a synergistic effect on 14.3, 92.9, 100, 16.7 and 100% of MBL-, OXA-23-, OXA-24-like-, OXA-51-like- and OXA-58-producing CRAb isolates, respectively. In the time–kill assay, imipenem and BLI-489 showed synergy against OXA-24-like-, OXA-51-like- and OXA-58-, but not OXA-23-producing CRAb isolates after 24 h. The in silico docking analysis showed that BLI-489 could bind to the active sites of OXA-24 and OXA-58 to confer strong inhibition activity. The combination of imipenem and BLI-489 exhibited synergistic effects for the rescue of CRAb-infected C. elegans and mice. Conclusions: Imipenem combined with BLI-489 has synergistic effects against CHDL-producing CRAb isolates.